Insights on Late-Stage COVID-19 Pandemic Recovery From a 21-Country Online Survey - Ewald, Louisa; Bellettiere, John; Farag, Tamer H.; Lee, Kristina M.; Palani, Sidhartha; Castro, Emma; Deen, Amanda; Gillespie, Catherine W.; Huntley, Bethany M.; Tracy, Alison; Haensch, Ana-Carolina; Kreuter, Frauke; et al. (International Journal of Public Health, 2025)
Background: The COVID-19 pandemic's impact on global health systems, economies, and societies necessitates comprehensive data for recovery strategies. The Pandemic Response Survey (PRS), conducted across 21 countries from March to May 2023, assessed impacts on healthcare, vaccine confidence, trust, and socio-economic indicators using online surveys.Methods: Utilizing the Facebook Active User Base for gender-stratified sampling, the PRS, in 15 languages, applied non-response and inverse propensity score weights for representativeness.Findings: From 621,000 responses (43% completion rate), significant disparities were observed. High life satisfaction was reported in Egypt, Nigeria, Colombia, and Mexico (70-80%), in contrast to Indonesia, Türkiye, and Viet Nam (20-30%). Food insecurity was significant in Nigeria, South Africa, and Colombia (50%), versus less than 10% in Italy, Japan, and Germany. Vaccine confidence and trust in government varied markedly, underlining the need for tailored interventions. Interpretation: The PRS highlights online surveys' effectiveness in guiding pandemic recovery, emphasizing targeted policies to tackle disparities. Collaborative data collection and international knowledge sharing are vital for effective strategies.